Administrative Appeals in Romania and Poland - A Topical Comparative Perspective - Dacian C. DRAGOŞ; Mariusz SWORA; Andrzej SKOCZYLAS (Transylvanian Review of Administrative Sciences, 2012)
The article focuses on the issue of administrative appeal and analyzes how the appeal functions in two different jurisdictions: Poland and Romania. The authors start by providing information on the nature of the administrative appeal (mandatory or not), deadlines for exercising it, suspensive effect for the action in court etc. All these aspects are examined from a comparative perspective. The aim of the comparative perspective is to highlight that currently the European national systems are fluid and continuously changing; in addition, the goal is to identify best practices that could be transferred from one system to the other. One of the key topics addressed in the context of this theme refers to the relationship that exists between the administrative appeal and the action in court. Authors try to answer the question whether the citizens’ access to justice is breached in cases when the appeal is mandatory. The authors also discuss the fact that very often a mandatory appeal can lead to a high number of cases being solved outside the courts.